Crown‐Ether‐Based Cryptands with Rarely Strong Affinities for Binding Neutral Organic Molecules. Issue 33 (8th March 2022) - Tan, Yanyan; Pan, Shaowu; Zhang, Shilong; Fang, Lin; Zhang, Feichun; Zhang, Yuanyuan; Jiang, Lasheng
Abstract: Herein, we present the syntheses of two new crown‐ether‐based cryptands and their complexation behaviors with neutral organic molecules. The interactions between 4 /5 and G1 /G2 were fast exchange systems forming pseudorotaxane‐like complexes with a 1 : 1 stoichiometric ratio. The association constant ( K a ) of "long‐armed" cryptand 5 with G2 was even up to 2.5×10 5  M −1, which is 10 to 10 3  times higher than the previously reported host‐neutral guest system to the best of our knowledge. Such a large K a is even comparable to that of reported cryptands with secondary ammonium salts and paraquat derivatives. Thorough studies demonstrated that excellent spatial fitting and multi non‐covalent interactions (H‐bonding and π–π stacking) are essential for such a large K a . Abstract : The ′iterative approach′ of delicately tunning the non‐covalent interactions could be a powerful route to construct molecular hosts that exhibit high selectivity and affinity for guest molecules. Through tailoring spatial fitting and multi non‐covalent interactions (especially H‐bonding), cryptands with rarely strong affinities for binding neutral guest molecules were achieved.